The Challenges of Teaching World Belief Systems in an Educate Together School Setting: A Case Study - Sutton, Rebecca (My University, 2018)
A shift is taking place in Irish primary schools throughout the country. As a result of immigration, globalisation, and the desire for change from Irish parents, Irish schools have required to examine how they approach teaching world belief systems. Through the ‚ÄòBelief Systems‚Äô strand, in the Learn Together curriculum, Educate Together National Schools have been approaching the subject for a number of years. Therefore, the primary aim of this research project was to explore the attitudes and experiences that teachers, in one specific Educate Together school, have on teaching belief systems. The research design used was a qualitative method. The research carried out was a case-study, with semi-structured interviews taking place with several teachers from one Educate Together school in County Dublin. Grounded theory was used for data analysis. Findings indicate positive attitudes towards the Learn Together curriculum and the strong need for teacher‚Äôs awareness towards particular diversity within a qualified homogeneous setting. This study aims to inform teachers about the benefits and challenges that arise from approaching world belief systems in a qualified homogeneous primary school setting.
Professional Master of Education.
Keywords: Research Subject Categories; World belief systems.; Learn Together curriculum; Educate Together School; Homogeneous primary school setting.